The Effect of Government Expenditure And Economic Growth on The Human Develovment Index in Riau Province - Jumatul Haj; Nawarti Bustamam (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This study aims to analyze the effect of Government Expenditure and Economic Growth on the Human Development Index (HDI) in Riau Province. HDI is used as an indicator to measure the level of community welfare from aspects of education, health, and standard of living. The method used is multiple linear regression with secondary data processed using the E-Views 10 program. The results show that partially, government expenditure has a positive and significant effect on HDI in Riau Province during the 2010–2023 period, while economic growth has a positive but not significant effect. Simultaneously, both variables have a significant effect on HDI in Riau Province during the 2010–2023 period. These findings indicate the important role of government expenditure in improving the quality of life of the population.